Naturally occurring benzophenones and xanthones from Garcinia smeathmannii (Planch. & Triana) Oliv. displayed anti-inflammatory effects by modulating the activities of inflammatory mediators in LPS-stimulated RAW 264.7 macrophages - Jeelani, Mohammed; Fouotsa, Hugues; Mohammed, Osama A.; Alfaifi, Jaber; Adebayo, Salmon; Ahmed, Mohammad Muzammil; Yahia, Amar Ibrahim Omer; Eissa, Hanan; Bahashwan, Emad; Mohammed, Nahid Ahmed; Alotaibi, Yousef Ayesh; Asiri, Ashwaq Yahya; et al. (Frontiers in Pharmacology, 2024)
Introduction: There is a growing interest in studying natural products for the identification of novel lead compounds for drug development for treating inflammatory diseases. Although some studies have focused anti-inflammatory activity of benzophenones and xanthones, exploring additional targets such as enzymes and cytokines, involved in their inflammatory response could provide more comprehensive understanding of the compounds’ anti-inflammatory effects. In this study, four xanthones ananixanthone (1), smeathxanthone A (2), smeathxanthone B (3), and 1,3,5,8-tetrahydroxy-2-(3-methybut-2-enyl)-4-(3,7-dimethyloct-2,6-dienyl) xanthone (4); and three benzophenones guttiferone O (5), guttiferone M (6), and aristophenone A (7) from Garcinia smeathmannii (Planch. & Triana) Oliv. were investigated for their effect on nitric oxide production, cyclooxygenase, lipoxygenase inhibition, and Th1/Th2 cytokines production in activated RAW 264.7 macrophages. Methods: The Griess reagent method and the ferrous oxidation-xylenol orange assay were used to evaluate the inhibition of NO production and the 15-lipoxygenase activity respectively. Cyclooxygenase activity was assessed using the fluorometric COX activity assay kit and measurement of Th1/Th2 cytokines was performed using a flow cytometer. Results: All the tested compounds exhibited a dose-dependent inhibition of NO production with varying degrees of inhibitory effects on 15-LOX activity. Compound (6), displays the best inhibitory effect on COX-1/COX-2 activity. A general trend of the tested compounds on cytokines profiles revealed that compound (5) showed a pronounced enhancement of anti-inflammatory cytokines (IL-4 and IL-10). Conclusion: This observation supports future exploration of ananixanthone (1), guttiferone O (5), and guttiferone (6) as potential candidates for the development of anti-inflammatory drugs.